CRITICAL DISCOURSE ANALYSIS ON ONLINE NEWS TEXT OF PUBLIC FIGURES DURING COVID-19 PANDEMIC IN INDONESIA - Rafii, Muhammad (Jurnal Review Pendidikan dan Pengajaran, 2024)
This study set out to describe the format of news articles regarding prominent celebrities that hosted big crowds of their fans during the COVID-19 pandemic on detiknews.com and anteraceh.com. Using a qualitative research method was the approach taken in this study. Detik and Anteroaceh, which were both online, were used to gather the data. The news article's headline read: “Jejak Kasus Picu Kerumunan Selebgram Herlin Kenza hingga Jadi Tersangka”, “Kerumunan saat selebgram ini tiba di Lhokseumawe langgar PPKM, Satgas Covid ; kami tidak tau”, and “Selebgram Herlin Kenza divonis bersalah kasus kerumunan, Jaksa : Tak bayar denda, penjara 2 bulan” This study looked at the events that made Herlin Kenza a well-known public figure and led to large gatherings of people during the Corona virus outbreak. The three-dimensional structures text in CDA established by Teun A. van Dijk method, which comprises of micro structure, macro structure, and super structure, was used in the current study.. The results demonstrated that the first and second news of the public figure "Herlin Kenza" contain thematic and topical aspects in a micro structure that demonstrates the public appeals made. Superstructure is a term used to describe the way the scheme is used to structure the news. The primary actor, Herlin Kenza, is indisputable, but there will be a sizable number of people present in the crowds. The macro structure, on the other hand, comprises of semantics with background, detail, and intent elements that describe the events and context of the story of Herlin Kenza, who drew a large crowd during the COVID-19 pandemic.